Perceptions of Mental Health Help-Seeking Among Christian Individuals in Indonesia - Justus Efraim Wowor; Evans Garey (Faculty of Psychology, Universitas Semarang, 2024)
The prevalence of individuals seeking mental health support and undergoing treatment in Indonesia remains notably low. Religious contexts significantly influence an individual’s understanding of mental health literacy, perceptions of mental well-being, and help-seeking behaviors. This study investigates the perceptions of mental health help-seeking, depression, and treatment among Christian individuals in Indonesia. The research participants consisted of 34 Christian individuals aged 18–25 years, representing the emerging adulthood stage. Data were collected using the story completion method and analyzed through reflexive thematic analysis. Member checking was employed as a credibility measure. The study identified nine main themes and seven sub-themes that encapsulate perceptions related to help-seeking, depression, and treatment. Furthermore, two themes emerged within one of the main themes concerning help-seeking perceptions. Keywords: Christianity; Depression; Mental health; Perception; Story completion